Chaucer, Humanism, and Printing: Conditions of Authorship in Fifteenth-Century England. - Carlson, David R. (University of Toronto Quarterly)
Discusses the conditions of authorship in 15th century England and how they affect English poet Geoffrey Chaucer. Marketing of printers' work; Manuscript book trade in England; Chaucer's authorial self-consciousness; Import of his place of burial.